Context Based Learning: Introducing Newer Learning Approach In Nursing - DR.P.MANGALA GOWRI; DR.M.A.SAHBANATHUL MISSIRIYA (International Journal of Pharma and Bio Sciences, 2015)
In the present scenario, the learning method should be brainstorming. In order to promote a newer approach in nursing education context based learning method introduced at Saveetha College of Nursing. From IV year BSc(N), 60 students were selected by random sampling. In experimental group 30 students were divided into 5 equal groups. To provide community health care, students were posted in the urban community as a team for one week. Each group was allotted with one facilitator. Group discussion was done on the need and care of the family along with facilitator. All members of the family were taken care by the group of students at a time for 5 days. Finally the knowledge, skill and attitude of students were evaluated. The results showed that there was significant improvement in experimental group than control.